Mood Investigation in the Motivational Quotes of the Instagram Reels - Afdhalina; Ayu Indari (Institute of Computer Science (IOCS), 2022)
Human beings had many struggles in their lives that must be survived in the problematic situation. Many ways to healing were the alternative in the problem solving. The motivational quotes came to stimulate the soul to rise back in the slope of enlightenment. Nowadays, the social media is as bridge to gain the information especially in Instagram reels. The platform to share daily life is a media to find many motivational quotes. The quotes contain a linguistic aspect especially in the mood system. The aim of this study was to investigate the mood investigation in the motivational quotes of the Instagram reels. This study applied the content analysis method. The data was obtained from two accounts of Instagram reels, namely @quotes and @merciful_path. The result of this study could be seen that declarative was the dominant of mood investigation the motivational quotes of the Instagram Reels because especially in the motivational quotes consisted of the provocation words to attract people attentions and contain complete functions which was easy to deliver the message for people. They needed to create the functional structure word organization not only the grammatical rules but also the semantic area.